Peningkatan Kompetensi Mengajar Pendidikan Jasmani melalui Perbaikan Pilihan Spektrum Gaya Mengajar Model Mosston - Agus Kristiyanto; Agus Margono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This study was designed to formulate effective method in improving students’ competencies through Mosston’s model of teaching style spectrum. The design of the study were classroom action research. The subjects were students of health and sport education FKIP UNS. The results showed that the action improved subjects’ sensitivity about students’ need, goal achievement, and subject matter.